Decentralisation and forest management in Latin America: towards a working model - Larson, A.M. (2003)
The particular characteristics of natural resources make the decentralisation of their management to elected local governments even more complex than the decentralisation of services and infrastructure. Nevertheless, natural resources are equally importnat to rural development concerns in the Third World. Numerous countries have begun to implement policies for some for some forms decentralisation involving natural resources and the environment, and many local governments are already making decisions that affect the future of local resources. This article reviews experiences with decentralisation of forest management in Bolivia, Brazil, Costa Rica, Guatemala, Honduras and Nicaragua. Based on those experiences, it proposes a working model for more effective decentralisation strategies. The model addresses the legal structure for decentralised forest management and relevant variables that define the local decision-making sphere, as well as key mediating factors that also affect outcomes. Most of these variables, even in the local sphere, offer important sites for policy and aid intervention.